Extraction and purification of protease from silver catfish (Pangasius sutchi) viscera / Normah Ismail and Nurnajwa Aziz Jaafar - Ismail, Normah; Aziz Jaafar, Nurnajwa (2018)
Protease is the enzyme which can be extracted from plant, animal, and microorganism. About 60% enzymes widely used nowadays are proteases. The objectives of this study were to determine the proteolytic activity and molecular weight distribution of protease extracted from Pangasius sutchi silver catfish viscera. Crude protease was extracted in 10 mM Tris-HCL buffer at pH 8.0. Subsequently, the protease was partially purified in stages beginning from ammonium sulphate precipitation (60%) followed by dialysis and gel filtration chromatography. Fractions collected from gel filtration chromatography was freeze-dried and analysed for optimum temperature and pH. Results showed that the viscera contain 13.79% protein. The protease total activity was 344.08 U with specific activity of 31.92 U/mg, purification fold 3.5 and 63.16% percent recovery. The protease proteolytic activity was optimum at 60 °C and pH 6. This study indicated that purification steps involving ammonium sulphate precipitation at 60% saturation, gel filtration chromatography and freeze drying led to the production of Pangasius sutchi visceral protease with a relatively high proteolytic activity.